2019
DOI: 10.1002/pbc.27875
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of children with high‐risk acute myeloid leukemia who underwent allogeneic hematopoietic stem cell transplantation following complete remission with initial induction chemotherapy in the AML‐05 clinical trial

Abstract: In the AML-05 clinical trial conducted by the Japanese Pediatric Leukemia/Lymphoma Group from 2006 to 2010, children with high-risk acute myeloid leukemia (HR AML) received allogeneic hematopoietic stem cell transplantation (allo-HSCT) at first complete remission (CR1).The aim of this study was to investigate the impact of allo-HSCT on the outcome of HR AML.Patients with either monosomy 7, 5q−, t(16;21), Ph1, FLT3-ITD, or induction failure after the first course of chemotherapy were eligible for transplant. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In addition, a previous study showed that the 3-year OS rates among patients who underwent transplants at CR1 and CR2 were 73% and 25%, respectively. This study supported the notion that allo-HSCT maybe a suitable treatment for high-risk AML at CR1 [19].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, a previous study showed that the 3-year OS rates among patients who underwent transplants at CR1 and CR2 were 73% and 25%, respectively. This study supported the notion that allo-HSCT maybe a suitable treatment for high-risk AML at CR1 [19].…”
Section: Discussionsupporting
confidence: 86%
“…High-risk R/R childhood acute leukemia has a poor prognosis; allo-HSCT may provide effective treatment for afflicted patients [19][20][21]. In recent years, AD transplantation has made great progress in the treatment of childhood hematologic diseases [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…This strategy misses a substantial fraction of patients who need more intensive therapy, because 20–30% of “low-risk” patients relapse [ 1 , 4 ]. At the other end of the spectrum, 25–30% of high-risk patients who are transplanted in first remission die of relapse or toxicity [ 5 , 6 ]. Our goal is to define AML-microenvironment interactions that contribute to relapse and can be targeted pharmacologically.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with FLT3/ITD mutations accounted for 10.0% of overall FAB-M4/M5 cases and these were identi ed as an independent risk factor for relapse and survival. [29] reported the excellent effect of allogeneic HSCT for children with high-risk AML, and their results showed that the high-risk group could bene t from HSCT. In addition, haplo-HSCT was also found to have great promise for the treatment of children with FAB-M4/M5 in the current study.…”
Section: Discussionmentioning
confidence: 99%